2010
DOI: 10.1677/jme-10-0059
|View full text |Cite
|
Sign up to set email alerts
|

Expanding roles of NUCB2/nesfatin-1 in neuroendocrine regulation

Abstract: Nesfatin-1 was originally identified as a hypothalamic neuropeptide, derived from the precursor NEFA (for DNA binding/EF-hand/acidic protein)/nucleobindin 2 (NUCB2), with the ability to suppress food intake, acting in a leptin-independent manner. Departing from this seminal finding, the patterns of expression of NUCB2/nesfatin-1 have been thoroughly characterized in different hypothalamic nuclei and brain areas with proven roles in energy homeostasis, and its potential interactions with other key neuropeptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 42 publications
3
96
0
6
Order By: Relevance
“…Yet, as highlighted elsewhere in this review, experimental work in different species has also defined the important contribution of other central transmitters and peripheral hormones, such as glutamate, GABA, and ghrelin (just to name but a few examples) in the physiological control of puberty onset (72,73). A recent addition to the growing list of pubertal modulators is nesfatin-1, as revealed by recent data on pubertal female rats (74,75). The major features of this neuropeptide as a putative regulator of the timing of puberty in the female are summarized below and synoptically presented in Table 3.…”
Section: Nesfatin-1: Novel Player In the Metabolic Control Of Pubertymentioning
confidence: 92%
See 1 more Smart Citation
“…Yet, as highlighted elsewhere in this review, experimental work in different species has also defined the important contribution of other central transmitters and peripheral hormones, such as glutamate, GABA, and ghrelin (just to name but a few examples) in the physiological control of puberty onset (72,73). A recent addition to the growing list of pubertal modulators is nesfatin-1, as revealed by recent data on pubertal female rats (74,75). The major features of this neuropeptide as a putative regulator of the timing of puberty in the female are summarized below and synoptically presented in Table 3.…”
Section: Nesfatin-1: Novel Player In the Metabolic Control Of Pubertymentioning
confidence: 92%
“…Nesfatin-1 is one of the peptide products of the gene NUCB2, with the ability to conduct anorectic effects acting at central (hypothalamic) levels (75). The interest in the metabolic actions of this molecule was reinforced by the demonstration of its expression in hypothalamic areas with key roles in food intake control, such as the ARC, the paraventricular nucleus (PVN), and the lateral hypothalamus (LHA), and the fact that anorectic effects of nesfatin-1 appear to be independent of leptin signaling (75).…”
Section: Nesfatin-1: Novel Player In the Metabolic Control Of Pubertymentioning
confidence: 99%
“…In recent studies, increasing blood pressure effect of nesfatin-1 has been demonstrated (14,24,22). Yosten et al reported that intracerebroventricular injection of nesfatin 1 caused an increased blood pressure in rats (24).…”
Section: Discussionmentioning
confidence: 99%
“…Structural analyses revealed the presence of several conserved cleavage recognition sites for prohormone convertases (PC3/1 and PC2) within rat NUCB2/ nesfatin sequence, thus suggesting this to be a precursor that gives rise, by differential proteolytic processing, to several active pep-tides. The predicted (major) fragments of such processing were termed nesfatin-1, nesfatin-2, and nesfatin-3 (14,15). Nesfatin-2 and nesfatin-3, the fragments of NUCB2, have the same structure as the DNA structure of calcium binding proteins However, there is no information about the biological activity of these peptides (14,16,17,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation